The Relationship Between Principal Competency And School Culture Towards Teacher Performance In State Junior High School - Sen Sat Jantusen; Pakpahan, Betty A.S; Sitompul, Arip Surpi (Jurnal Ilmu Pendidikan dan Sosial, 2026)
This study aims to analyze 1) the relationship between principal competence and teacher performance at Public Junior High School Technical Implementation Units (UPTs) in Doloksanggul District; 2) the relationship between school culture and teacher performance at Public Junior High School Technical Implementation Units (UPTs) in Doloksanggul District; and 3) the relationship between principal competence and school culture and teacher performance at Public Junior High School Technical Implementation Units (UPTs) in Doloksanggul District. This study used a quantitative method with an ex post facto or survey approach. The population was all 182 teachers at Public Junior High School Technical Implementation Units (UPTs) in Doloksanggul District. Using the Slovin formula with a 10% margin of error, a sample of 65 teachers was taken. Data were collected with a closed questionnaire consisting of 22 statement items for variable X1 (Principal Competence) and 40 statement items for variable X2 (School Culture) and 28 statement items to measure variable Y (Teacher Performance), so that the total was 90 statement items. Before being used on real respondents, the instrument was first tested on 30 teachers of UPT SMP Negeri 001 Pasar Doloksanggul outside the sample. The results of the instrument trial, all questionnaire items were valid and reliable. Data analysis techniques were carried out using descriptive analysis, variable categorization and parametric statistical analysis with the Pearson correlation test and the coefficient of determination test. The results of the data analysis showed that: 1) There is a positive and significant relationship between Principal Competence and Teacher Performance at UPT SMP Negeri throughout Doloksanggul District in 2026 with a correlation value of R or rhitung = 0.661 and a relationship contribution of 43.7% with a Sig value of 0.000 <0.05 and thitung = 7.000> ttable (n-2 = 63) = 2,000. 2) There is a positive and significant relationship between School Culture and Teacher Performance in UPT SMP Negeri throughout Doloksanggul District in 2026 with a correlation value of R or rcount = 0.502, a relationship contribution of 25.2% and a Significance value of 0.000 <0.05 with tcount = 4.613> ttable (n-2 = 113) = 2.000 and 3) There is a positive and significant relationship between Principal Competence and School Culture together with Teacher Performance in UPT SMP Negeri throughout Doloksanggul District in 2026 with a correlation value of R = 0.711 and a relationship contribution of 50.5% with a Significance value of 0.000 <0.05 and Fcount = 31.634> Ftable (k-1, nk; 2.63) = 3.15. Thus it is concluded that the research hypothesis is accepted